Parental stress: a neglected entity - Inamdar, Nusrat R.; Tamboli, Anvesh S.; Mauskar, Anupama V.; Tamboli, Suchit (International Journal of Contemporary Pediatrics, 2019)
Background: Parents feel very stressed when their child is sick and in Intensive care unit. Objectives of study were to identify common parental stressors during their child’s critical illness and to examine its relationship with demographic variables. Methods: It’s a Cross-sectional questionnaire based study done in PICU & NICU of a tertiary care medical college hospital in Mumbai, 62 parents of children admitted to PICU and NICU for at least 24 hours were interviewed using the Parental Stress Scale. The demographic variables were also recorded. The data analyzed using Cluster Analysis, Kruskal Wallis test, Chi- square test and spearman correlation. Results: The main cause of parental stress was to witness the child’s sufferings (unresponsiveness/pain, procedures, tubes, monitors around child) (median of standardized score = 3.9, IQR = 0.5, p <0.005). The median of standardised stress score due to hospital environmental factors (monitor alarms, nurses, doctors around baby, other sick children) was 3.7 (IQR = 0.5) and that due to lack of intimacy with child was 3.6 (IQR =0.4). Age of parent inversely correlated with the level of stress (r = -0.638) and parents of infants were more stressed (p = 0.005). Number of children, socioeconomic status didn’t affect the stress levels. Conclusions: Young parents and parents of infants were more stressful. Socioeconomic status, residential area and parental sex didn’t affect stress. Few stress factors need remedial steps to meet parental needs. The clinician’s awareness about these stressors, may help to provide optimized family-directed care.